Health Problems and Associated influence factors among Health Care workers during COVID-19 Pandemic: A Systematic Review and Meta-analysis - Seydaduong Them; Xun Huang; Marady Hun; , Shi Wu Wen; Aizhong Liu; Surotul Ilmiyah (International Nutrition and Health Administrations Journal, 2023)
Purpose: This systematic review aims to investigate the health problems and associated influence factors among HCWs during COVID-19. Methods: A systematic search was conducted in the database of Embase, PubMed, Web of Science, and Google Scholar between January and May 2023. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method were used. Review Manager 5 and STATA 15.1 software were used to identify the pooled prevalence, the sensitivity analysis, and the publication bias of the outcomes. NOS was used to assess the quality appraisal of the eligible studies. Results: A total of 6,878 participants were surveyed across the 10 studies. The studies were between March 5, 2020, and June 30, 2021. The ten eligibility studies conducted in 9 countries were included. The pooled prevalence of depression across 10 studies was 30%(95%CI: 19%-40%), the pooled prevalence of anxiety was 35%(95%CI: 21%-48%) across 9 studies, the pooled prevalence of insomnia was 47%(95%CI: 42%, 51%) across 4 studies, the pooled prevalence of PTSD, stress, EE, DP, and a PA, was 9%(95%CI: -5%, 22%), 64%(95%CI: 60%, 67%), 34%(95%CI: -10%,69%), 17%(95%CI: 14%, 21%), 54%(95%CI: 51%, 57%), respectively across 2 studies by a random effects model. The study also identified various influential factors associated with these health problems. Conclusion: The systematic review highlights the including depression significance of mental health, physical health problems, and other problems among HCWs during the pandemic, , anxiety, stress, PTSD, insomnia, burnout (exhaustion, DP, PA), and workload.